The challenges and possibilities of public access defibrillation. (12th February 2018) - Ringh, M.; Hollenberg, J.; Palsgaard‐Moeller, T.; Svensson, L.; Rosenqvist, M.; Lippert, F. K.; Wissenberg, M.; Malta Hansen, C.; Claesson, A.; Viereck, S.; Zijlstra, J. A.; Koster, R. W.; et al.
Abstract: Out‐of‐hospital cardiac arrest (OHCA) is a major health problem that affects approximately four hundred and thousand patients annually in the United States alone. It is a major challenge for the emergency medical system as decreased survival rates are directly proportional to the time delay from collapse to defibrillation. Historically, defibrillation has only been performed by physicians and in‐hospital. With the development of automated external defibrillators (AEDs), rapid defibrillation by nonmedical professionals and subsequently by trained or untrained lay bystanders has become possible. Much hope has been put to the concept of Public Access Defibrillation with a massive dissemination of public available AEDs throughout most Western countries. Accordingly, current guidelines recommend that AEDs should be deployed in places with a high likelihood of OHCA. Despite these efforts, AED use is in most settings anecdotal with little effect on overall OHCA survival. The major reasons for low use of public AEDs are that most OHCAs take place outside high incidence sites of cardiac arrest and that most OHCAs take place in residential settings, currently defined as not suitable for Public Access Defibrillation. However, the use of new technology for identification and recruitment of lay bystanders and nearby AEDs to the scene of the cardiac arrest as well as new methods for strategic AED placement redefines and challenges the current concept and definitions of Public Access Defibrillation. Existing evidence of Public Access Defibrillation and knowledge gaps and future directions to improve outcomes for OHCA are discussed. In addition, a new definition of the different levels of Public Access Defibrillation is offered as well as new strategies for increasing AED use in the society.